Validating a Patient-Reported Comorbidity Measure with Respect to Quality of Life in End-Stage Renal Disease. - Maxi Robinski; Franz Strich; Wilfried Mau; Matthias Girndt (PLoS ONE, 2016)
PURPOSE:Medical record-derived comorbidity measures such as the Charlson Comorbidity Index (CCI) do not predict functional limitations or quality of life (QoL) in the chronically ill. Although these shortcomings are known since the 1980s, they have been largely ignored by the international literature. Recently, QoL has received growing interest as an end-point of interventional trials in Nephrology. The aim of this study is to compare a patient-reported comorbidity measure and the CCI with respect to its validity regarding QoL. METHODS:The German Self-Administered Comorbidity Questionnaire (SCQ-G) was completed by 780 adult end-stage renal disease-patients recruited from 55 dialysis units throughout Germany. Acceptance was evaluated via response rates. Content validity was examined by comparing the typical comorbidity pattern in dialysis patients and the pattern retrieved from our data. Convergent validity was assessed via kappa statistics. Data was compared to the CCI. Linear associations with QoL were examined (criterion validity). RESULTS:The SCQ-G was very well accepted by dialysis patients of all ages (response rate: 99%). Content validity can be interpreted as high (corresponding comorbidity items: 73.7%). Convergent validity was rather weak (.27≤ρ≤.29) but increased when comparing only concordant items (.39≤ρ≤.43). With respect to criterion validity, the SCQ-G performed better than the CCI regarding the correlation with QoL (e.g., SF-12-physical: SCQ-G total score: ρ = -.49 vs. CCI: ρ = -.36). CONCLUSIONS:The patient-reported measure proved to be more valid than the external assessment when aiming at insights on QoL. Due to the inclusion of subjective limitations, the SCQ-G is more substantial with respect to patient-centered outcomes and might be used as additional measure in clinical trials.